Subhiksha: A Battle for Survival - Kalia, Sumedha; Kalia, Rishi (Indian Journal of Marketing, 2011)
In a developing country like India, a large chunk of consumer expenditure is on basic necessities, especially food related items. The Indian retail industry is the fifth largest in the world. And when we throw light on this retail sector, then broadly, we have two divisions - Organized and Unorganized retail traders. Though initially, the retail industry in India was mostly unorganized, however, with the change of tastes and preferences of the consumers, the industry is getting more popular these days and getting organized as well. The Indian retail industry is expected to grow from 35,000 crore in 2004-05 to 109,000 crore by the year 2010. According to the 8th Annual Global Retail Development Index (GRDI) of AT Kearney, Indian retail industry is the most promising emerging market for investment. In 2007, the retail trade in India had a share of 8-10% in the GDP (Gross Domestic Product) of the country. In 2009, it rose to 12%. It is also expected to reach 22% by 2010. Kishore Biyani’s - Pantaloons and Big Bazaar are on top on the list, and we have Tata group, RPG group, Reliance etc. They have contributed to the Indian retail by being pioneers and reshaping the retail landscape in the country by adapting to conditions in the country. But unfortunately, the post was triggered by the news that Subhiksha closed down their 1600 outlets. In this case, study efforts have been made to grasp the business strategy of Subhiksha and despite of best human and non-human capital, why it became a sunk ship.